Manajemen Peserta Didik Man 1 Pulang Pisau Plus Keterampilan - Salbiah Salbiah; Simint Simint; Samsullaili Samsullaili (Journal on Education, 2024)
The aim of this research is to determine the student management process and to improve student management at Madrasah Aliyah Negeri 1 Pulang Pisau. This research uses a descriptive analysis method to describe each process carried out, including understanding, learning, and in-depth study, which is applied at MAN 1 Pulang Pisau. Management and related arrangements or management. In education, Management is a measure of success in the educational process to achieve goals. Students are very important for an educational institution, especially Islamic boarding schools, because they have a big role as educational subjects. Management is a measure of success in the educational process to achieve goals. Students are very important for an educational institution, especially Islamic boarding schools, because they have a big role as educational subjects.